Perbandingan Pertanggungjawaban Hukum antara Bentuk Badan Usaha Terbatas (PT) dan Perusahaan Perorangan - Naily Aridah; Rewidan Muhammad Haikal (IPM2KPE, 2024)
The aim of the research is to identify the comparison of legal liability between limited business entities (PT) and individual companies. This research uses a normative legal approach with descriptive analysis characteristics. Data collection was carried out through secondary data sources, specifically by applying library research techniques, known as